On Gide's PROMETHEE : Private Myth and Public Mystification - Weinberg, Kurt (Book collections on Project MUSE., 1972)
Through a careful rendering of the text, deciphering its hidden ironies, Mr. Weinberg sees Promethee as a modern allegory, a parable wrought of allusions, symbols, and images drawn from classical antiquity and calvinist theology, and a multi-leveled sotie à miroirs. Originally published in 1972. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable.